Variation in Bariatric Surgery Costs and Complication Rates in the Military Health System. Issue 7 (28th December 2019) - Luan, William Patrick; Leroux, Todd C; Olsen, Cara; Robb, Douglas; Skinner, Jonathan S; Richard, Patrick
Abstract: Introduction: Within the Military Health System (MHS), facilities have struggled to meet minimum recommended volume thresholds for certain procedures. Understanding variations in complication rates and cost can help policymakers tailor policy to target improvement. Our objective was to quantify the variation in bariatric surgery complication rates and costs across a sample of military hospitals. Materials and Methods: We study a retrospective cohort of 38 military surgeons practicing in 21 military treatment facilities from 2007 to 2014 who performed 1, 277 bariatric surgeries. Data from the Centralized Credentials and Quality Assurance System, which provides education and training characteristics of physicians, were linked to patient encounter data from the MHS Data Repository. Physicians were included if they performed at least five bariatric surgeries over the study period. Patients were included if they had a diagnosis of obesity (body mass index > 30) and underwent a bariatric weight loss surgery. We calculated and summarized inpatient costs and complication rates across both surgeons and facilities using multivariable mixed-effects linear or logistic models. We used these models to calculate adjusted complication rates and average costs across both providers and hospitals to characterize variation in bariatric outcomes within the MHS. This study was considered exempt by the Uniformed Services University Institutional Review Board. Results: We find evidence of large variations in both complication rates and costs per admission. Overall, we found a 15.5% complication rate across the sample. When comparing averages across facilities, we find large variation in complications (49.4% coefficient of variation [CV]) and procedure costs (25.9% CV). Controlling for patient comorbidities, BMI, and year attenuates much of the variation (12.6% CV complications, 4.4% CV cost), but cannot completely explain differences across facilities. Our model suggests that complications cost 32% more than complication-free surgeries on average suggesting that quality improvement efforts could potentially yield large savings. Conclusions: We find large variations in complication rates even after controlling for patient health. Furthermore, surgical complications are a significant determinant of cost. Policymakers should target efforts to improve surgical quality across facilities and physicians. Surgical quality improvement initiatives could produce savings to the MHS through reduced complications and improved surgical readiness.